The Effect of Age, Gender According to Types and Duration of Diabetes among Patients in Al-Nasiriyah City - Oudah, Shamam (Journal of Biomedicine and Biochemistry, 2024)
Background A cross-sectional study including patients visiting the Di- abetes and Endocrinology Center in the city of Nasiriyah. The ages of patients range from 12 to 75 years. The study was conducted between February 12, 2023 and March 27, 2023. The study used 100 patients with chronic diabetes as samples. The patients were divided into two groups: the first group included 50 patients with known diabetes, and the second group included 50 people without diabetes as a control group. They were reviewed at the Diabetes and Endocrinology Center in Nasiriyah. Purpose of the study was determine the relationship between the con- structed model and self-administered blasting method were used to gen- erate data. Closely relevant socio-demographic questions (age, gender, occupation, family history, body mass index, marital status and residence) were still included in the questionnaire . The study also included com- paring the levels of the glycated hemoglobin A1c marker and the fasting plasma glucose level in relation to gender, age and duration in different forms of diabetes.Conclusion Problems can arise from this metabolic disease, including oral cavity problems. Patients’ quality of life may be affected by oral problems, which are a major side effect of diabetes.